Association of Dyslipidemia and Sex With Coronary Artery Calcium Assessed by Coronary Computed Tomography Angiography - Asami, Masahiko; Horiuchi, Yu; Kato, Nahoko; Tanimoto, Shuzou; Hara, Kazuhiro; Aoki, Jiro; Tanabe, Kengo; Yamaji, Kyohei; Watanabe, Mika; Furui, Koichi (International Heart Journal, 2017)
Previous studies reporting that statin increases coronary artery calcium (CAC) were conducted exclusively on patients with statin as a prevention, regardless of the presence or absence of dyslipidemia. The impact of sex on CAC has not been fully evaluated. We aimed to determine the association of dyslipidemia and sex with CAC using 320-row multi-detector computed tomography (MDCT).Of the 356 consecutive patients who underwent coronary MDCT, 251 patients were enrolled, after excluding those with prior stenting and/or coronary bypass grafting or images showing motion artifacts. The primary outcome measures were the percent calcium volume (PCV) and percent atheroma volume (PAV) per coronary vessel.Multivariable analyses indicated that PCV was significantly higher in dyslipidemia patients without statins than in the subjects without dyslipidemia [partial regression coefficient (PRC): 2.59, 95% confidence interval (CI): 0.83 to 4.34, P = 0.004]. In contrast, PCV was similar in dyslipidemia patients taking statins and those without dyslipidemia (PRC: -1.09, 95% CI: -2.82 to 0.65, P = 0.22). There was no significant difference in PCV between men and women, although women exhibited a significantly lower PAV (PRC: -2.87, 95% CI: -4.54 to -1.20, P = 0.001).In low-risk patients, these results could be translated into hypotheses, which should be tested in future prospective studies. Furthermore, there was no significant difference in CAC between men and women, but women had lower PAV than men.